2022
DOI: 10.1093/jas/skac421
|View full text |Cite
|
Sign up to set email alerts
|

Short-term consumption of the mycotoxin zearalenone by pubertal gilts causes persistent changes in the histoarchitecture of reproductive tissues

Abstract: Consumption of zearalenone (ZEN) detrimentally affects tissues and systems throughout the body, and these deleterious effects are especially pronounced in swine. The objectives of this project were to determine the effects of short-term consumption of ZEN (at concentrations that could be found on-farm) on growth, carcass weight, liver weight and reproductive tissues of pubertal gilts, and to determine if the effects are transient or persistent. Cross-bred gilts (107.25 ± 2.69 kg) were randomly assigned to one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…ZEN can cause reproductive disorders in different animals due to the similar chemical structure to estrogen. Numerous types of research have shown the adverse effect of reproduction induced by ZEN, including the swollen vulva, vaginal prolapse, pseudopregnancy, infertility, and abortion [ 11 , 12 , 13 , 14 ]. Moreover, studies have shown that ZEN also could inhibit biomolecule synthesis and cell proliferation in different cell lines [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…ZEN can cause reproductive disorders in different animals due to the similar chemical structure to estrogen. Numerous types of research have shown the adverse effect of reproduction induced by ZEN, including the swollen vulva, vaginal prolapse, pseudopregnancy, infertility, and abortion [ 11 , 12 , 13 , 14 ]. Moreover, studies have shown that ZEN also could inhibit biomolecule synthesis and cell proliferation in different cell lines [ 15 ].…”
Section: Introductionmentioning
confidence: 99%